Hot holiday fling - Wood, Joss (Harlequin desire, 2020)
"Sparks fly the moment Adie Ashby-Tate and Hunt Sheridan meet. Too bad Hunt doesn't do relationships. But career-minded Adie, working with him to boost her business, is too tempting for the millionaire influencer to resist. When she agrees to a no-strings tryst, he jumps at the chance. The only rule: no commitment. But the Christmas spirit might change all the rules..."--